2020
DOI: 10.51920/jd.v10i1.154
|View full text |Cite
|
Sign up to set email alerts
|

PERENCANAAN STRATEGIS SISTEM INFORMASI KLINIK KECANTIKAN DENGAN PENDEKATAN WARD AND PEPPARD MODEL (Studi Kasus : PT. Virgina Estetika(Farina Beauty Clinic))

Abstract: PT.Virgina Estetika (Farina Beauty Clinic) merupakan organisasi atau perusahaan yang bergerak di bidang penyedia jasa pelayanan perawatan kulit wajah dan tubuh. Untuk bisa mendapatkan keunggulan bersaing dan dapat bertahan dalam persaingan yang ketat, strategi yang dapat dilakukan Klinik kecantikan adalah dengan differentiation dan cost reduction. Salah satu hal yang bisa dilakukan untuk cost- reduction adalah dengan menjadikan proses bisnis yang ada di Klinik Kecantika menjadi lebih efisien, salah satu hal ya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Research related to the method of Ward and Peppard is found in research [9] [10] which aims to analyse the application of SI / IT in government agencies by producing a proposed application portfolio only. Then in research [11] [12] [13] [14] [6] aims to analyse the use of SI / IT that can be used in their respective companies due to the need to realign the use of SI / IT. In research [15] [16] conducted the use of SI / IT in the school or education sector to develop SI / IT strategic planning because at this time there is no alignment between the vision and mission and the use of SI / IT.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research related to the method of Ward and Peppard is found in research [9] [10] which aims to analyse the application of SI / IT in government agencies by producing a proposed application portfolio only. Then in research [11] [12] [13] [14] [6] aims to analyse the use of SI / IT that can be used in their respective companies due to the need to realign the use of SI / IT. In research [15] [16] conducted the use of SI / IT in the school or education sector to develop SI / IT strategic planning because at this time there is no alignment between the vision and mission and the use of SI / IT.…”
Section: Methodsmentioning
confidence: 99%
“…DPKPP Tasikmalaya Regency is also currently an agency that has not shown the formation of good egovernment, because DPKPP Tasikmalaya Regency is an agency that has only carried out mergerization for 2 years so that the need for SI / IT planning for SI / IT alignment in each field can be in accordance with the vision, mission, and objectives of the Tasikmalaya Regency DPKPP agency so that later it has a clear SI / IT planning roadmap for the long term [1] Strategic planning is a series of steps that are arranged systematically by conducting a comprehensive analysis to develop an action plan so that organizational goals are achieved [5]. Strategic Planning is also the ability to identify and evaluate the impact of using Information Technology as a formulation of overall business strategy [6]. The method that can be used in strategic planning is the Ward and Peppard method because this method is a comprehensive method, meaning that this method starts from analyzing the internal environment and external environment so that later it can formulate strategies that are in accordance with the organization's business objectives [7] [8].…”
Section: Introductionmentioning
confidence: 99%
“…Menurut Riswan dan Fasa (2016) mengasumsikan bahwa metode First In First Out (FIFO) adalah barang yang pertama kali dibeli adalah barang yang pertama kali dijual, sehingga harga pokok barang yang dibeli pertama kali sama dengan harga pokok barang yang terjual (Septiana, Y. 2017).…”
Section: Pendahuluanunclassified
“…The equivalent noise level is one of the calculations of the sound pressure level where a certain value of sound that fluctuates over a certain time is equivalent to a steadystate sound level at the same time interval (Haryanto, 2011) The average sound pressure level over time (Leq) can be found through the following equation: Information: Leq : equivalent noise level (dB) N : number of parts measured Li : noise level (dBA) Nn : frequency of occurrence of Ln (noise level According to the International Labour Organization (ILO), noise is a source of unwanted sound originating from production process equipment and / or work equipment at a certain level can cause hearing loss (Laziardy, 2017). According to (Septiana, 2017) There is a relationship between noise intensity and noise-induced hearing loss in workers exposed to noise. According to the Minister of Manpower and Transmigration (2011) on NAB in the workplace, the noise NAB of 85 dBA is set as the highest intensity and is a value that is still acceptable to workers without causing illness or health hearing loss in daily work for a time not exceeding 8 hours a day or 40 hours a week.…”
Section: Equivalent Noise Levelmentioning
confidence: 99%